Delivering Substance Abuse and Child Welfare Content Through Interactive Television - David Hollister, Gloria McGee (Research on Social Work Practice, Vol. 10 No. 4, July 2000 417-427, 2000)
To evaluate interactive television (ITV) for delivering a graduate course on substance abuse and child welfare to distant sites. Method: Students'ratings of instructor-student communication are compared across distance and resident sites for the ITV course and with students in the traditional course. Similar comparisons are made for tudents'ratings of the amount learned and for instructors'judgments of student performance. Distance and resident students'ratings of the ITV course are also compared to traditional courses. Results: The mean of the instructor-student communication dimensions was the same for distance and traditional students and was slightly more positive for distance students compared to resident students. Student performance and course grades were similar across groups, and the distance and resident students in the ITV course rated it as helpful to their learning as traditional courses. Conclusions: The results suggest that ITV compromised neither instructor-student communication nor the amount that students learned